The Effectiveness of Aloe Vera in Multiple Moist Spray Products as a Hair Tonic to Reduce Students Scalp Irritation - Setiawan, Mochammad Agung Dhani (Jurnal Kesehatan Komunitas Indonesia, 2024)
Skin irritation on the scalp is often experienced by men. This happens due to the high increase in sebum production and frequent use of excessive products like pomade. For men with sensitive scalp, this causes hair problems such as dandruff. Proper hair care can help manage dandruff, including the use of a hair tonic containing aloe vera. This research aims to investigate the influence of aloe vera content on dandruff treatment. The study design employed pre-experimental research with a pre-post test group, involving a population of 23 respondents and a sample of 23 respondents selected through total sampling. Statistical analysis utilized paired t-tests with significance set at <0.05. Results from 23 respondents indicated that 19 respondents (82.6%) experienced a decrease in scores, while 4 respondents (17.4%) showed an increase. Statistical analysis revealed significant results with a p-value of 0.000 < 0.05. The conclusion drawn is that the aloe vera content in Multiple Moist Spray has a beneficial effect on treating dry dandruff. Therefore, individuals with dandruff are encouraged to be selective in choosing scalp treatments.